Gambaran Pengetahuan Gizi, Pola Makan Mie Instan dengan Status Gizi Mahasiswa Papua Universitas Halu Oleo - Agnes Risma Ronsumbre; Wa Ode Salma; Harleli Harleli (Pusat Riset dan Inovasi Nasional, 2025)
Nutritional knowledge is knowledge about food and nutrients, sources of nutrients in food, food that is safe to consume so that it does not cause disease and how to process food properly so that the nutrients in food are not lost and how to live healthily. One of the factors that influences eating patterns is the level of nutritional knowledge. A person's level of nutritional knowledge influences eating behavior in choosing food which determines whether it is easy for a person to understand the benefits of the nutritional content of the food consumed. The aim of this research is to determine the relationship between nutritional knowledge and instant noodle eating patterns among Papuan students at Halu Oleo University. This research uses quantitative research and the type of research is observational analytics with a cross sectional design. The results showed that the majority of respondents had a poor level of nutritional knowledge (75%), while only 25% of respondents had high nutritional knowledge. This shows that even though students are in a higher education environment, their knowledge about nutrition still needs to be improved. Most respondents (52%) consume instant noodles 2-3 times a week, with the main reasons being ease of preparation (65%) and affordable price (20%). This consumption is more dominant among students who live in boarding houses or dormitories compared to those who live with their families. It is hoped that this research will be useful for subjects to balance their eating patterns and have self-control because the majority of subjects have uncontrolled eating patterns due to living in boarding houses or dormitories so that their body health continues to be maintained. Apart from that, subjects can also pay more attention to nutritional balance in consuming food in order to achieve optimal nutritional status.